PEMBERDAYAAN KELOMPOK USAHA TANI DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT (Studi Di Desa Kampani Kecepatan Wadaga Kabupaten Muna Barat) - Haspianti, Wa Ode; Kasim, Syaifuddin S.; Jabar, Aryuni Salpiana (WELL-BEING: Journal of Social Welfare, 2020)
The purpose of this study was to determine the stages of the implementation of the empowerment of farming groups in an effort to improve community welfare in Kampani Village, Wadaga District, West Muna Regency. The method used in this research is through field research by using interview and observation techniques to empower farming groups in an effort to improve community welfare. The results showed that the implementation of the empowerment of farming groups in an effort to improve the welfare of the community by fostering a desire to change. Develop the ability to participate, increase the role in the desire for empowerment and also the development of motivations for change.